Early Parenting Practices, Child School Readiness and Early Academic Performance - Conica, Mirela (Trinity College Dublin. School of Psychology. Discipline of Psychology, 2024)
School readiness and early academic achievement are fundamental to children¿s long-term academic performance, as well as social, physical, and mental health later in life. Thus, one salient goal for educators, researchers and policymakers is to identify and subsequently promote factors that ensure children are well equipped to benefit from education upon school entry. As it is well established, development is driven by children¿s interaction with their social environment across time. During the formative years preceding school entry, children¿s social environment primarily comprises interacting with mothers and fathers. It follows that the type of parenting practices in which mothers and fathers engage with their child prior to formal education is fundamental for children¿s school readiness and early academic functioning. Although the crucial role that parents play for child development is well recognised, understanding which parenting practices should be encouraged to promote school readiness is challenging, largely arising from the lack of an agreed upon definition of school readiness and early achievement. Do children depend on literacy and numeracy skills to perform well academically or is it their social competence that enables learning and achievement? Further, do parents and educators concur with regards to the types of skills they endorse in order to prepare children for school? A comprehensive understanding of how early parenting practices relate to child academic performance can only be achieved insofar as careful consideration is given to these persistent questions. Accordingly, the present thesis aims to first systematically review the existent parenting and school readiness research base to (1) gain insight into how school readiness has been conceptualised within the developmental field and (2) to identify the types of parenting practices that have been empirically linked with outcomes indicative of school readiness. Second the thesis undertakes a series of individual studies based on primary and secondary data analysis to examine longitudinal associations between aspects of early parent-child interaction that have theoretical relevance to early academic achievement, but have been empirically examined to a lesser extent, and children¿s indices of school readiness and early scholastic performance. Chapter 1 discusses the importance of school readiness and early academic achievement, the defining properties of school readiness and the conceptual and methodological challenges associated with it. Chapter 2 outlines the importance of parent-child interaction for child development, mechanisms of parenting influence and their effect on child development. Chapter 3 provides an overview of the current research base on the longitudinal association between parenting practices and child school readiness through a systematic review. Findings indicated that school readiness was primarily assessed in terms of child language, literacy, numeracy, cognition, socioemotional and behavioural competence and by global measures of school readiness. The review further indicated that parenting related to these outcomes either directly (via parent-child interaction) or indirectly (via the home learning environment; HLE). Of the direct mechanisms, the most examined aspect was parental sensitivity, followed by cognitive stimulation or a combination of both. Of the indirect pathways, the majority of studies focused on the HLE with a negligible number examining parent involvement in early childhood education. Findings of this review were used to inform the remainder of the studies in this thesis. Chapter 4 provides an outline of the methodology employed by each individual study. Chapter 5 presents four studies based on primary data analysis which examine direct mechanisms of parenting during toddlerhood and preschool years that relate to children¿s language, literacy and numeracy, cognition, and socioemotional development during middle childhood. Specifically, Study 1 in Chapter 5 examines how parent-child linguistic alignment at all levels of language structure relate to child language quality and complexity, verbal comprehension, and literacy skills. Findings indicate that both parents aligned with children to a similar extent and there was some evidence to suggest that parents engaged in complementary alignment. Children also aligned their language to that of their parents in similar proportions. The systematic review further suggested that language use during parent-child interaction can also influence child numeracy skills. Therefore, Study 2 in Chapter 5 first described maternal, paternal, and children¿s use of one type of language, decontextualised language during toddlerhood and preschool years. The study further explored associations between the use of decontextualised language in toddlerhood and preschool years and children¿s literacy and numeracy skills in middle childhood. Findings indicated that maternal decontextualised language during toddlerhood was negatively linked with child reading skills in middle childhood, but the reverse was observed in preschool years; maternal decontextualised language during mother-pre-schooler interaction was positively associated with child reading skills suggesting that the benefits of decontextualised language may become apparent later in development. Mothers¿, fathers¿, and children¿s decontextualised language during preschool years was also positively linked with child numeracy in middle childhood. A further linguistic mechanism that has emerged as important to child development is contingent conversational turn-taking. However, this process has primarily been examined in relation to child language development despite theoretical arguments which also implicate it in cognitive growth. Accordingly, Study 3 in Chapter 5 examined how mother-father-child contingent turn-taking in toddlerhood and preschool years related to child executive functioning in middle childhood. Findings attest to the importance of engaging children in meaningful conversation and communicating with the child rather than at the child. Results also tentatively suggest that fathers may play a particularly important role with respect to the development of children¿s executive processes. The semantic connectedness between conversational turns that parents and children engage in also have theoretical relevance to children¿s socioemotional competence. Arguably, meaningfully connected back-and-forth exchanges are foundational for pragmatic and social development. Therefore, with the aim of examining the role of this process to children¿s socioemotional outcomes, Study 4 in Chapter 5 examined how connected conversational turns in toddlerhood and preschool years during triadic mother-father-child interaction related to children¿s socioemotional difficulties in middle childhood. Findings suggested that contingent turn-taking during toddlerhood, but not preschool years, was linked with fewer socioemotional difficulties. As such, results indicate that toddlerhood may represent a particularly fertile period during which parents can buffer against socioemotional problems. Chapter 6 presents two studies based on secondary data analysis which investigate indirect mechanisms of parenting influence. Specifically, Study 1 in Chapter 6 employed structural equation modelling of Growing Up in Ireland (GUI) data (national longitudinal cohort study of children in Ireland) to examine how the formal literacy (e.g., teaching the alphabet) and numeracy (e.g., teaching counting) as well as the informal literacy (e.g., reading to child) and numeracy (e.g., playing board games) environment at three years related to child vocabulary, pragmatic language, literacy and numeracy and socioemotional skills at five- and nine-years-old. The study revealed that only the informal literacy and numeracy environment demonstrated both domain-specific and cross-domain positive effects on children¿s language and numeracy outcomes but not on socioemotional outcomes, at five- and nine-years-old. These results suggest that even casual cognitively stimulating activities that do not directly focus on active teaching may benefit children¿s educational outcomes. Study 2 in Chapter 6 explored another element of the HLE by characterising paternal and child language use during a shared reading interaction with wordless and text-based picture books. The study found that the text-based picture book elicited greater paternal language quality, more language that extended the topic, and more conversational utterances. In contrast, the wordless picture book elicited more labelling and descriptive utterances. Thus, different book types may be useful in eliciting distinct aspects of paternal language input during father-child interaction. The study further found that children¿s language quantity was greater in the wordless picture book condition whereas their language quality was greater in the text-based condition. Moreover, fathers¿ language with both book types showed differential links with children¿s language quantity, complexity, and quality. The study therefore provides preliminary evidence that variation in book content may encourage different types of learning with distinct effects on different domains of child language. Finally, Chapter 7 synthesises the findings of all studies included in this thesis, outlines the strengths and limitations of the thesis, discusses theoretical and practical implications of findings, and concludes with suggestions for future research directions.
APPROVED